SURGICAL MANAGEMENT OF INJURIES TO THE SMALL AND LARGE INTESTINE - Saydullaev Zayniddin Yakhshiboyevich; Murtazaev Zafar Isrofulovich; Narzullaev Shokhrukh Shukhratovich; Khaidarov Numonzhon Bazar ugli (Scholar Express Journals, 2023)
The article presents the experience of surgical treatment of 50 patients with isolated injuries of the small and large intestine. The diagnostic algorithms used in the clinic in patients with injuries of the small and large intestine were studied. The diagnostic program included history taking, clinical and objective data, results of ultrasonic and roentgenologic methods of investigation, videolaparoscopy. Depending on the nature of the injury, indications for surgical treatment of patients with this pathology were specified. The developed diagnostic program and the choice of an optimal variant of the operative intervention allowed to reduce the number of unfavorable outcomes among the injured with small and large intestine injuries.
Keywords: trauma; small intestine; large intestine; diagnosis